Papillary Tumor of the Pineal Region: Case Report and Literature Review - Yamaki, Vitor Nagai; Vera, Felipe Romero; Ribeiro, Renan Ribeiro; Medeiros, Raphael Salles Scortegagna; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Papillary tumor of the pineal region (PTPR) is a neuroectodermal tumor thought to originate from cells of the subcommissural organ. Its oncologic properties are still under investigation, as well as the most suitable therapeutic measures for this type of neoplasm. We report the case of a 36-year-old woman with a 1-year history of headache and intermittent diplopia. The magnetic resonance imaging (MRI) scan showed a heterogeneously enhancing mass in the pineal region that caused an acute hydrocephalus, and an emergency shunt derivation was necessary. One week later, the patient was submitted to subtotal tumor resection, and remained asymptomatic in the post-operative period. In the follow-up, the patient remained asymptomatic; in the imaging control 3.5 years after the surgical resection, local recurrence was identified, and the patient was submitted to a local radiation protocol. Our literature review showed an early clinical onset due to intracranial hypertension signs. Definitive clinical onset might be reached only through a histopathological examination. Gross total resection followed by radiotherapy is the current standard of care. Local recurrence is often observed, with rare dissemination to the cerebral spinal fluid. The natural history of the PTPR remains unknown, as well as the best treatment strategy. Large case series with longer follow-ups are necessary for further conclusions.
Keywords: pineal gland; brain tumor; surgical procedures; local recurrence